Coating composition, separator, electrochemical device, and electronic device

By using a coating composition containing fiber material and filler particles on the membrane of the electrochemical device, the safety problems caused by thermal shrinkage of the membrane are solved, the thermal safety and high-temperature cycling performance of the electrochemical device are improved, and the low-temperature impedance is reduced .

CN119231097APending Publication Date: 2024-12-31NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202411627506.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The thermal shrinkage of the separator in the electrochemical device when the positive and negative electrode sheet is short-circuited may lead to an increase in the short-circuit contact area, affecting the safety of the electrochemical device.

Method used

Using a coating composition containing fiber material and filler particles, at least one of the fiber material and filler particles contains a miscellaneous element, such as nitrogen or phosphorus, and the mass percentage of the miscellaneous element is between 10% and 60%, forming a support. The framework structure improves the thermal shrinkage and mechanical strength of the diaphragm, reduces porosity, enhances adhesion, and improves the thermal safety and high-temperature cycling performance of electrochemical devices.

Benefits of technology

It improves the thermal shrinkage and mechanical extrusion resistance of the diaphragm, enhances the thermal safety and high-temperature cycling performance of the electrochemical device, reduces the low-temperature impedance, and ensures the safety and performance stability of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231097A_ABST
    Figure CN119231097A_ABST
Patent Text Reader

Abstract

Provided are a coating composition, a separator, an electrochemical device, and an electronic device, the coating composition including a fiber material, filler particles, and a binder, the fiber material including at least one of a first inorganic ceramic or a first organic matter containing a miscellaneous element, the fiber material comprises at least one of a first inorganic ceramic and a second organic matter containing a hetero-element, the filler particles comprise at least one of a second inorganic ceramic and a second organic matter containing a hetero-element, at least one of the fiber material and the filler particles is an organic matter containing a hetero-element, the hetero-element comprises a nitrogen element or / and a phosphorus element, and the mass percentage of the hetero-element is 10%-60% based on the mass of the coating composition. When the coating composition is applied to the diaphragm, the diaphragm is coated with the coating composition to form a coating, so that the thermal safety and high-temperature cycle performance of the electrochemical device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to a coating composition, a diaphragm using the coating composition, an electrochemical device using the diaphragm, and an electronic device using the electrochemical device. Background Art

[0002] As portable chemical energy sources, electrochemical devices (such as lithium-ion batteries) are widely used in consumer electronics (such as mobile phones, notebooks, cameras, etc.), energy storage products (such as home energy storage, energy storage power stations, UPS power supplies, etc.) and new energy vehicles due to their high energy density, high operating voltage platform, low self-discharge, long service life and environmental friendliness.

[0003] The electrochemical device includes a diaphragm, which is crucial to the safety of the electrochemical device. Inorganic materials such as ceramic-coated diaphragms can improve the heat resistance of the diaphragm. However, when a short circuit occurs between the positive and negative electrodes, a large amount of heat is generated instantaneously. The diaphragm shrinks due to heat, which may cause continuous contact between the positive and negative electrodes and increase the short-circuit contact area, affecting the safety of the electrochemical device. Summary of the invention

[0004] The present application provides a coating composition, a separator, an electrochemical device and an electronic device.

[0005] The present application provides a coating composition, including a fiber material, filler particles and a binder, wherein the fiber material includes at least one of a first inorganic ceramic or a first organic matter containing a heteroelement, the filler particles include at least one of a second inorganic ceramic or a second organic matter containing a heteroelement, at least one of the fiber material and the filler particles is an organic matter containing a heteroelement, the heteroelement includes nitrogen and / or phosphorus, and the mass percentage of the heteroelement is 10% to 60% based on the mass of the coating composition.

[0006] The coating composition provided by the present application, when the coating composition is applied to the diaphragm, the coating composition is applied to the diaphragm to form a coating, and the fibrous fiber material in the coating plays the role of supporting the skeleton in the coating, improving the thermal shrinkage and stability of the diaphragm, and improving the mechanical extrusion resistance test performance of the diaphragm, and improving the overall hardness of the electrochemical device. The filler particles are filled between the gaps of the fiber material, reducing the porosity of the entire diaphragm, improving the mechanical strength and thermal shrinkage of the entire diaphragm, and facilitating the binder to fully bond the fiber material and the filler particles, improve the bonding force of the diaphragm, and improve the interface stability between the diaphragm and the positive and negative electrode materials, thereby facilitating the improvement of the rate performance of the electrochemical device. The combination of the above-mentioned fiber material and filler particles is also conducive to reducing the density of the coating, which is conducive to reducing the low-temperature impedance of the electrochemical device. At the same time, combined with the presence of nitrogen and / or phosphorus in the coating, it is conducive to constructing an organic coating framework structure, which is conducive to improving the stability of the pole piece, and improving the thermal safety and high temperature cycle performance of the electrochemical device. In the present application, the content of the impurity element is in the range of 10% to 60%, which is conducive to further improving the stability of the positive electrode sheet, so that the electrochemical device has good high-temperature cycle performance. If the mass percentage of the impurity element is large, such as greater than 60%, at a certain content, the mass percentage of the impurity element increases, which will increase the content of the fiber material or filler particles, thereby reducing the amount of binder used, the peeling force between the diaphragm and the positive and negative electrode sheets, and reduce the thermal shrinkage of the diaphragm, reducing the thermal safety of the electrochemical device.

[0007] Based on the first aspect, in some embodiments, the mass percentage of the impurity elements in the coating composition is 15% to 45%, which further improves the thermal safety and high temperature cycle performance of the electrochemical device.

[0008] Based on the first aspect, in some embodiments, the ratio of the length to the width of the fiber material is (3-50): 1. This facilitates easy dispersion during the preparation of the coating composition slurry, and facilitates the control of the roughness of the coating composition applied to the surface of the diaphragm so that the coating maintains a certain adhesion, thereby improving the high temperature cycle performance and rate performance of the electrochemical device.

[0009] Based on the first aspect, in some embodiments, the length of the fiber material is 2 μm to 50 μm. When preparing the coating composition slurry, it is beneficial to improve the dispersibility, and it is also beneficial to adjust the thickness of the coating when the coating composition is applied to the diaphragm, and reduce the increase in the thickness of the coating due to the long length of the fiber material, reduce the energy density of the electrochemical device, and at the same time, the long length of the fiber material will also increase the roughness of the coating on the surface of the diaphragm, and form some gaps on the surface of the diaphragm, thereby reducing the bonding force between the diaphragm and the positive and negative electrode sheets, thereby reducing the high temperature cycle performance and rate performance of the electrochemical device.

[0010] Based on the first aspect, in some embodiments, the particle size Dv50 of the filler particles is 0.1 μm to 3 μm. When the coating composition is applied to the diaphragm, it has a suitable thickness, which is beneficial for maintaining a high volume energy density of the electrochemical device and reducing the probability of the filler particles blocking the pores of the diaphragm, thereby improving the cycle performance of the electrochemical device.

[0011] Based on the first aspect, in some embodiments, the mass ratio of the fiber material to the filler particles is 1: (1-10). The mass ratio of the two is within the above range, which is conducive to the filler particles in the coating composition being able to fully fill the gaps between the fiber materials, and when the coating composition is applied to the diaphragm and forms a coating on the diaphragm, it is conducive to reducing the porosity of the coating, further improving the mechanical strength and thermal shrinkage of the diaphragm, and improving the thermal safety performance of the electrochemical device.

[0012] Based on the first aspect, in some embodiments, in the coating composition, the mass ratio of the sum of the fiber material and the filler particles to the binder is 99: 1 to 85: 15. Adding an appropriate amount of binder to the coating composition can bond the fiber material and the filler, and is also used to maintain a certain bonding force between the separator and the positive and negative electrode sheets when the coating composition is applied to the separator, thereby improving the rate performance of the electrochemical device.

[0013] Based on the first aspect, in some embodiments, the first organic matter includes at least one of ammonium polyphosphate, piperazine pyrophosphate, melamine polyphosphate, polyacrylonitrile, melamine, melamine thiocyanate or melamine cyanurate. The above organic compounds all have a fibrous structure and contain hetero elements. When the coating composition is applied to the diaphragm to form a coating, the above organic matter plays the role of supporting the skeleton in the coating, improves the thermal shrinkage and stability of the diaphragm, and improves the mechanical compression resistance test performance of the diaphragm, and improves the overall hardness of the electrochemical device. At the same time, the crystals of the above organic matter also grow along the long axis direction of the fiber, which can reduce the thermal shrinkage of the diaphragm, and at high temperatures, the above organic matter will also decompose, which has a flame retardant effect.

[0014] Based on the first aspect, in some embodiments, the first inorganic ceramic includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, aluminum oxide, boehmite, titanium dioxide, aluminum silicate, silicon carbide or silicon nitride. The above inorganic ceramics all have a fibrous structure, which not only helps to increase the mechanical strength of the diaphragm, but also plays a role in supporting the skeleton, which helps to further improve the mechanical extrusion resistance test performance of the diaphragm.

[0015] Based on the first aspect, in some embodiments, the second organic matter includes at least one of polyacrylonitrile, ammonium polyphosphate, melamine, dicyandiamide, melamine cyanurate, melamine thiocyanate or melamine polyphosphate. The above organic matter contains hetero elements, and on the basis of containing hetero elements, it also serves as a filler to further improve the mechanical extrusion resistance test performance of the diaphragm, and the above organic matter has good thermal stability, which is beneficial to improving the thermal safety performance of the electrochemical device and reducing the high-temperature storage expansion of the electrochemical device.

[0016] Based on the first aspect, in some embodiments, the second inorganic ceramic includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium niobium oxide, aluminum oxide, boehmite, or magnesium hydroxide. The use of solid electrolytes in the above inorganic ceramics can improve the mobility of lithium ions in the electrochemical device, reduce the low-temperature impedance of the electrochemical device, and improve the low-temperature cycle performance of the electrochemical device; the use of aluminum oxide, boehmite, and magnesium hydroxide is more conducive to improving the mechanical strength of the diaphragm.

[0017] Based on the first aspect, in some embodiments, the binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber, isocyanate, polyvinyl alcohol or sodium carboxymethyl cellulose. The above binder can fully bond the fiber material and the filler particles to improve the bonding force of the separator.

[0018] The second aspect of the present application also provides a diaphragm, which includes a base film and a coating located on at least one surface of the base film, wherein the coating includes the coating composition, and can improve the thermal shrinkage and stability of the diaphragm.

[0019] Based on the second aspect, in some embodiments, the porosity of the separator is 35% to 50%, so that the electrochemical device has a lower internal resistance and a good cycle retention rate.

[0020] Based on the second aspect, in some embodiments, the thickness of the coating is 0.3 μm to 5 μm, so that the separator can reduce the internal resistance of the electrochemical device while maintaining a certain resistance to thermal shrinkage, thereby taking into account both the thermal safety performance and the cycle performance of the electrochemical device.

[0021] The third aspect of the present application also provides an electrochemical device, comprising a positive electrode sheet and a negative electrode sheet, and the electrochemical device also includes a diaphragm, the diaphragm is located between the positive electrode sheet and the negative electrode sheet. The diaphragm includes a coating composition to improve the thermal safety performance and high temperature cycle performance of the electrochemical device.

[0022] The fourth aspect of the present application provides an electronic device, comprising the electrochemical device. The diaphragm comprising the coating composition improves the thermal safety performance and high temperature cycle performance of the electrochemical device, thereby facilitating the improvement of the safety performance and service life of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 , (a) is a schematic diagram of the cross-sectional structure of the coating composition of the present application applied to a diaphragm; (b) is a schematic diagram of the surface structure of the coating composition of the present application applied to a diaphragm.

[0024] Figure 2 This is a scanning electron microscope image of the coating on the surface of the base film in Example 1-1 of the present application.

[0025] Figure 3 for Figure 2 Scanning electron micrograph at higher magnification.

[0026] Figure 4 This is a scanning electron microscope image of the coating on the surface of the base film in Examples 1-2 of the present application.

[0027] Figure 5 This is a scanning electron microscope image of the coating on the surface of the base film in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0028] The technical scheme in the embodiment of the present application is described clearly and in detail below. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0029] As used herein, the term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values ​​are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values ​​explicitly designated as range limits, but also all individual numerical values ​​or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.

[0030] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" or "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" or "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0031] One embodiment of the present application provides a coating composition, including a fiber material, filler particles and a binder, the fiber material includes at least one of a first inorganic ceramic or a first organic matter containing a heteroelement, the filler particles include at least one of a second inorganic ceramic or a second organic matter containing a heteroelement, at least one of the fiber material and the filler particles is an organic matter containing a heteroelement, the heteroelement includes nitrogen and / or phosphorus, and the mass percentage of the heteroelement based on the mass of the coating composition is 10% to 60%.

[0032] The coating composition provided by the present application, when the coating composition is applied to the diaphragm, the coating composition is applied to the diaphragm to form a coating, and the fibrous fiber material in the coating plays the role of supporting the skeleton in the coating, improving the thermal shrinkage and stability of the diaphragm, and improving the mechanical extrusion resistance test performance of the diaphragm, and improving the overall hardness of the electrochemical device. The filler particles are filled between the gaps of the fiber material, reducing the porosity of the entire diaphragm, improving the mechanical strength and thermal shrinkage of the entire diaphragm, and facilitating the binder to fully bond the fiber material and the filler particles, improve the bonding force of the diaphragm, and improve the interface stability between the diaphragm and the positive and negative electrode materials, thereby facilitating the improvement of the rate performance of the electrochemical device. The combination of the above-mentioned fiber material and filler particles is also conducive to reducing the density of the coating, which is conducive to reducing the low-temperature impedance of the electrochemical device. At the same time, combined with the presence of nitrogen and / or phosphorus in the coating, it is conducive to constructing an organic coating framework structure, improving the stability of the positive and negative electrode sheets, and improving the thermal safety performance and high temperature cycle performance of the electrochemical device.

[0033] Compared with a single sheet-like structure and a filler coating containing impurity elements, the combination of the fiber material and the filler particles and at least one of them containing impurity elements in the present application reduces the thermal shrinkage of the diaphragm, reduces the impedance of the diaphragm, and improves the discharge capacity and cycle performance of the electrochemical device; compared with a single fiber material containing impurity elements, the combination of the fiber material and the filler particles and at least one of them containing impurity elements reduces the thermal shrinkage of the diaphragm and improves the thermal safety performance of the electrochemical device.

[0034] In the scanning electron microscope of the fiber material, the fiber material may have a columnar or rod-like structure. Each particle of the columnar or rod-like structure in the fiber material has a length and a width.

[0035] Among them, the content of the impurity elements is in the range of 10% to 60%, which is conducive to further improving the stability of the positive electrode sheet, so that the electrochemical device has good high-temperature cycle performance and thermal safety performance. If the mass percentage of the impurity elements is large, such as greater than 60%, at a certain content, the mass percentage of the impurity elements increases, which will increase the content of fiber materials or filler particles, thereby reducing the amount of binder used, reducing the peeling force between the diaphragm and the positive and negative electrode sheets, reducing the thermal shrinkage of the diaphragm, and reducing the thermal safety performance of the electrochemical device. In some embodiments, the mass percentage of the impurity elements in the coating composition is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any value within the range composed of any two of the above values.

[0036] In some embodiments, further, the mass percentage of the impurity elements in the coating composition is 15% to 45%, and more preferably, the mass percentage of the impurity elements is 20% to 45%.

[0037] In some embodiments, the ratio of the length to the width of the fiber material is (3~50):1. When the ratio of the length to the width of the fiber material is within the above range, it is easy to disperse in the process of preparing the coating composition slurry, and it is easy to control the roughness of the coating composition applied to the surface of the diaphragm so that the coating maintains a certain adhesion, thereby improving the high temperature cycle performance and thermal safety performance of the electrochemical device. If the ratio of the length to the width of the fiber material is small, the density of the coating composition applied to the surface of the diaphragm will increase, affecting the impedance of the diaphragm in the electrochemical device, and reducing the rate performance of the electrochemical device. If the length of the fiber material is too long and the ratio of the length to the width is small, it is not easy to disperse in the process of preparing the coating composition slurry, and the length of the fiber material is also easy to be interrupted, affecting the supporting role of the fiber material in the coating composition, and reducing the mechanical extrusion resistance test performance of the diaphragm. In some embodiments, the ratio of the length to the width of the fiber material can be 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or any value within the range composed of any two of the above values. Preferably, the ratio of the length to the width of the fiber material is in the range of 3 to 30, and further preferably in the range of 3 to 20.

[0038] In some embodiments, the length of the fiber material is 2 μm to 50 μm. When preparing the coating composition slurry, it is beneficial to improve the dispersibility, and it is also beneficial to adjust the thickness of the coating when the coating composition is applied to the diaphragm, and reduce the thickness of the coating due to the long length of the fiber material, thereby reducing the energy density of the electrochemical device. At the same time, the longer length of the fiber material will also increase the roughness of the coating on the surface of the diaphragm, forming some gaps on the surface of the diaphragm, thereby reducing the bonding force between the diaphragm and the positive and negative pole pieces, thereby reducing the thermal safety performance, high temperature cycle performance and rate performance of the electrochemical device. In some embodiments, the length of the fiber material can be 2 μm, 3 μm, 5 μm, 7 μm, 9 μm, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any value within the range of any two of the above values. In some embodiments, the length of the fiber material is 2 μm to 30 μm, and more preferably 2 μm to 15 μm.

[0039] In some embodiments, the particle size Dv50 of the filler particles is 0.1 μm to 3 μm. The particle size Dv50 of the filler particles maintains a suitable size and has a suitable thickness when the coating composition is applied to the diaphragm, which is beneficial for the electrochemical device to maintain a high volume energy density, and also helps to reduce the probability of the filler particles blocking the pores of the diaphragm, thereby improving the cycle performance of the electrochemical device. In some embodiments, the particle size Dv50 of the filler particles can be 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3 μm or any value within the range of any two of the above values. Preferably, the particle size Dv50 of the filler particles can be 0.2 μm to 2 μm, and more preferably 0.3 μm to 1 μm.

[0040] In some embodiments, the mass ratio of the fiber material to the filler particles is 1:(1-10). The mass ratio of the two is within the above range, which is conducive to allowing the filler particles to fully fill the gaps between the fiber materials in the coating composition. When the coating composition is applied to the diaphragm and forms a coating on the diaphragm, it is conducive to reducing the porosity of the coating, further improving the mechanical strength and thermal shrinkage of the diaphragm, and improving the thermal safety performance of the electrochemical device. The mass ratio of the fiber material to the filler particles can be 1:1, 1:2, 1:4, 1:6, 1:7, 1:8, 1:9, 1:10 or any value within the range formed by any two of the above values.

[0041] In some embodiments, in the coating composition, the mass ratio of the sum of the fiber material and the filler particles to the binder is 99:1 to 85:15. Adding an appropriate amount of binder to the coating composition can bond the fiber material and the filler, and is also used to maintain a certain bonding force between the diaphragm and the positive and negative electrode sheets when the coating composition is applied to the diaphragm, thereby improving the rate performance of the electrochemical device. If the mass of the binder accounts for a large proportion, it may reduce the permeability of the diaphragm, increase the internal resistance, and affect the rate performance of the electrochemical device. In some embodiments, in the coating composition, the mass ratio of the sum of the fiber material and the filler particles to the binder can be 99:1, 99:5, 90:6, 90:10, 80:10, 85:15 or any ratio within the range of any two of the above values.

[0042] In some embodiments, the first organic matter includes at least one of ammonium polyphosphate, dicyandiamide, piperazine pyrophosphate, melamine polyphosphate, polyacrylonitrile, melamine, melamine thiocyanate or melamine cyanurate. The above organic compounds all have a fibrous structure and contain heteroelements. When the coating composition is applied to the diaphragm to form a coating, the above organic matter plays the role of supporting the skeleton in the coating, improves the thermal shrinkage and stability of the diaphragm, and improves the mechanical extrusion resistance test performance of the diaphragm, and improves the overall hardness of the electrochemical device. At the same time, the crystals of the above organic matter also grow along the long axis direction of the fiber, which can reduce the thermal shrinkage of the diaphragm, and at high temperatures, the above organic matter will also decompose, which has a flame retardant effect.

[0043] In some embodiments, the first inorganic ceramic includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, aluminum oxide, boehmite, titanium dioxide, aluminum silicate, silicon carbide or silicon nitride. The above inorganic ceramics all have a fibrous structure, which not only helps to increase the mechanical strength of the diaphragm, but also plays a role in supporting the skeleton, which helps to further improve the mechanical extrusion resistance test performance of the diaphragm.

[0044] In some embodiments, the second organic matter includes at least one of polyacrylonitrile, ammonium polyphosphate, melamine, dicyandiamide, melamine cyanurate, melamine thiocyanate or melamine polyphosphate. The above organic matter contains hetero elements, and on the basis of containing hetero elements, it also serves as a filler to further improve the mechanical extrusion resistance test performance of the diaphragm, and the above organic matter has good thermal stability, which is beneficial to improving the thermal safety performance of the electrochemical device and reducing the high-temperature storage expansion of the electrochemical device.

[0045] In some embodiments, the second inorganic ceramic includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium niobium oxide, aluminum oxide, boehmite, or magnesium hydroxide. The use of solid electrolytes in the above inorganic ceramics can improve the mobility of lithium ions in the electrochemical device, reduce the low-temperature impedance of the electrochemical device, and improve the low-temperature cycle performance of the electrochemical device; the use of aluminum oxide, boehmite, and magnesium hydroxide is more conducive to improving the mechanical strength of the diaphragm.

[0046] In some embodiments, the binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber, isocyanate, polyvinyl alcohol or sodium carboxymethyl cellulose. The above binder can fully bond the fiber material and the filler particles to improve the bonding force of the separator.

[0047] The present application also provides a diaphragm, comprising a base film and a coating located on at least one surface of the base film, wherein the coating comprises the coating composition. The diaphragm comprising the coating has a good heat retention rate, a high porosity, and a high ionic conductivity, so that an electrochemical device comprising the diaphragm has a low impedance, a thermal safety pass rate, a high temperature cycle performance, and a low temperature cycle performance.

[0048] exist Figure 1 In (a), in the separator, a coating is formed on the surface of the base film, the coating contains a coating composition, the coating composition contains a fiber material (such as N prism-shaped fibers) and filler particles (such as three-dimensional fillers), combined with Figure 1 (b), the fiber material and the filler particles are evenly distributed, and the filler particles are filled between the fiber materials.

[0049] In some embodiments, the porosity of the diaphragm is 35% to 50%. Within this range, the electrochemical device has a low internal resistance and a good cycle retention rate. In some embodiments, the porosity of the diaphragm can be 35%, 38%, 40%, 43%, 45%, 48%, 50%, or any ratio within the range of any two of the above values.

[0050] In some embodiments, the thickness of the coating is 0.3 μm to 5 μm. The thickness of the coating is within the above range, so that the diaphragm reduces the internal resistance of the electrochemical device while maintaining a certain resistance to thermal shrinkage, thereby taking into account the thermal safety performance and cycle performance of the electrochemical device. In some embodiments, the thickness of the coating can be 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 1.8 μm, 2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or any ratio within the range composed of any two of the above values. Furthermore, the thickness of the coating is 1 μm to 3 μm.

[0051] In one embodiment of the present application, an electrochemical device is also provided, comprising a housing, an electrode assembly, and an electrolyte, wherein the battery cell and the electrolyte are located in the housing. The housing may be a packaging bag obtained by packaging with a packaging film (such as an aluminum-plastic film), such as when the electrochemical device is a soft-pack secondary battery. In other embodiments, the electrochemical device may also be a steel-shell battery, an aluminum-shell battery, and the like.

[0052] The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet. The electrode assembly may be a laminated structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet and then winding them.

[0053] Positive electrode The positive electrode plate includes a positive current collector and a positive active layer disposed on the positive current collector. The positive current collector may be aluminum foil or nickel foil, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and the polymer substrate. The positive active layer contains a positive active material, and the positive active material includes a compound that reversibly embeds and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive active material may include but is not limited to at least one of lithium cobaltate, lithium nickel manganese cobaltate, lithium nickel manganese aluminum, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate.

[0054] The positive electrode active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc. At least one of the above.

[0055] The positive electrode active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.

[0056] Negative electrode The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0057] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.

[0058] The negative electrode active material includes a material that reversibly intercalates / deintercalates lithium ions. In some embodiments, the material that reversibly intercalates / deintercalates lithium ions includes a carbon material. In some embodiments, the carbon material can be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable batteries. In some embodiments, the carbon material includes, but is not limited to: crystalline carbon, amorphous carbon, or a mixture thereof. Crystalline carbon can be amorphous, flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0059] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material includes, but is not limited to: lithium metal, structured lithium metal, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or any combination thereof. The silicon-carbon composite refers to a composite containing at least about 5 wt% silicon based on the weight of the silicon-carbon negative electrode active material.

[0060] In some embodiments, the negative electrode active material comprises at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon alloy, or silicon oxide.

[0061] When the negative electrode includes a silicon-carbon compound, based on the total weight of the negative electrode active material, silicon:carbon=about 1:10-10:1, and the median particle size Dv of the silicon-carbon compound is 50The negative electrode active material layer may be formed by evaporation, sputtering, plating, or the like. When the negative electrode comprises lithium metal, the negative electrode active material layer may be formed by, for example, a spherical, twisted conductive skeleton and metal particles dispersed in the conductive skeleton. In some embodiments, the spherical, twisted conductive skeleton may have a porosity of about 5% to about 85%. In some embodiments, a protective layer may be further provided on the lithium metal negative electrode active material layer.

[0062] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0063] In some embodiments, the conductive material includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0064] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof.

[0065] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include water, etc., but is not limited thereto.

[0066] Diaphragm The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0067] For example, the diaphragm may include a base film and a coating. The base film is a non-woven fabric, a film or a composite film having a porous structure, and the material of the base film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.

[0068] Electrolyte According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.

[0069] The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application can be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or ethyl propionate (EP).

[0070] In some embodiments, the organic solvent includes an ether solvent, for example, at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonyl imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB) or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0071] In one embodiment of the present application, an electronic device is further provided, and the electronic device includes an electrochemical device.

[0072] The electronic device of the present application is not particularly limited. In some embodiments, the electronic device of the present application includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0073] The present application is described below by specific examples and comparative examples. Those skilled in the art should understand that the preparation methods described in the present application are only examples, and any other suitable preparation methods are within the scope of the present application.

[0074] Example 1-1 (1) Preparation of diaphragm The solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3 [abbreviated as LATP], melamine polyphosphate fiber MPP and adhesive styrene butadiene rubber are mixed in a mass ratio of 60:30:10 to obtain a coating composition; deionized water is added to the coating composition and dispersed evenly to obtain a coating composition slurry. The particle size Dv50 of LATP is 500nm, the length of MPP fiber is 4μm, and the aspect ratio is 10:1.

[0075] The coating composition slurry is uniformly coated on one surface of a polyethylene-based film and dried in an oven to obtain a diaphragm.

[0076] (2) Preparation of lithium-ion batteries Preparation of positive electrode: The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) in a weight ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry. The positive electrode slurry is evenly coated on one side of the positive electrode collector aluminum foil, dried, and then the above steps are repeated on the other side of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active layer on both sides, which is then cold pressed and cut to obtain a positive electrode sheet.

[0077] Preparation of negative electrode sheet: The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber (SBR) are added to deionized water in a weight ratio of 96:2:2, and stirred evenly to form a negative electrode slurry. The negative electrode slurry is evenly coated on one side of the negative electrode collector copper foil, dried, and then the above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet coated with a negative electrode active layer on both sides, which is then cold pressed and cut to obtain a negative electrode sheet.

[0078] Preparation of electrolyte: Preparation of non-aqueous electrolyte: In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a weight ratio of 1:3:6 as a base solvent, and then fluoroethylene carbonate and LiPF6 were dissolved in the above base solvent to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, and the mass percentage of fluoroethylene carbonate is 5%.

[0079] Preparation of diaphragm: The diaphragm prepared in the above-mentioned embodiment 1 was selected.

[0080] Lithium-ion battery assembly: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator being located between the positive electrode sheet and the negative electrode sheet, to obtain a stacked electrode assembly. After welding the electrode ears, the electrode assembly is placed in an aluminum-plastic film packaging bag, heat-sealed on all sides, leaving a liquid injection port, and the above-mentioned electrolyte is injected. After vacuum packaging, standing, hot pressing, degassing and other processes, a lithium-ion battery is obtained.

[0081] (3) Preparation of symmetric battery: Different numbers of separator layers (1, 2, 3, 4, and 5 layers) were stacked respectively, with Cu foils being the positive and negative electrodes, and the same electrolyte as that of the above-mentioned lithium-ion battery was injected to obtain symmetrical batteries with different numbers of separator layers.

[0082] Example 1-2 The difference between Example 1-2 and Example 1-1 is that melamine cyanurate particles, melamine cyanurate fibers and adhesive styrene-butadiene rubber are mixed in a mass ratio of 60:30:10, and deionized water is added to disperse them uniformly to obtain a coating composition slurry. The remaining steps are the same as Example 1-1.

[0083] Examples 1-3 The difference between Example 1-3 and Example 1-1 is that dicyandiamide and solid electrolyte Li 1.3 Al 0.3 Ti 1.7The (PO4)3 fiber and the adhesive styrene-butadiene rubber were mixed in a mass ratio of 60:30:10, and deionized water was added to disperse them uniformly to obtain a coating composition slurry. The remaining steps were the same as those in Example 1-1.

[0084] Examples 1-4 The difference between Example 1-4 and Example 1-1 is that the ammonium polyphosphate particles, the aluminum oxide fibers and the adhesive styrene-butadiene rubber are mixed in a mass ratio of 60:30:10, and deionized water is added to disperse them uniformly to obtain a coating composition slurry. The remaining steps are the same as those of Example 1-1.

[0085] Examples 1-5 The difference between Example 1-5 and Example 1-1 is that polyacrylonitrile particles, ammonium polyphosphate fibers and adhesive styrene-butadiene rubber are mixed in a mass ratio of 60:30:10, and deionized water is added to disperse them uniformly to obtain a coating composition slurry. The remaining steps are the same as Example 1-1.

[0086] Example 1-6 to Example 1-11 The type or amount of the fiber material in the coating composition slurry is adjusted, wherein the mass ratio of the first inorganic ceramic and the first organic matter contained in the fiber material is 1:1; or the type or amount of the filler particles is adjusted, wherein the mass ratio of the second inorganic ceramic and the second organic matter contained in the filler particles is 1:1, thereby obtaining the corresponding coating composition slurry, and the specific preparation parameters can be referred to Table 1. The remaining steps are the same as those in Example 1-1.

[0087] Example 1-12 to Example 1-15 The ratio of the length to the width of the fiber material was changed, and the remaining steps were the same as those of Example 1-2.

[0088] Example 1-16 to Example 1-23 The types of fiber materials and filler particles in the coating composition were changed, and the mass proportion of the impurity elements was changed. The remaining steps were the same as those in Example 1-1.

[0089] Example 1-24 to Example 1-29 The length of the fiber material was changed, and the remaining steps were the same as in Example 1-18.

[0090] Example 1-30 to Example 1-34 The types of fiber materials and filler particles in the coating composition were changed, and the particle size Dv50 of the filler particles was changed. The remaining steps were the same as those in Example 1-1.

[0091] Embodiment 1-35 The type of adhesive was changed, and the remaining steps were the same as those in Example 1-1.

[0092] Example 2-1 to Example 2-8 The thickness of the coating or the porosity of the diaphragm was changed, and the remaining steps were the same as those in Example 1-1.

[0093] Comparative Example 1 The difference between Comparative Example 1 and Example 1-1 is that the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The (PO4)3 particles and the adhesive styrene-butadiene rubber were mixed in a mass ratio of 90:10, and deionized water was added to disperse them evenly to obtain a coating composition slurry. The remaining steps were the same as those in Example 1-1.

[0094] Comparative Example 2 The difference between Comparative Example 2 and Example 1-1 is that melamine cyanurate particles and adhesive styrene-butadiene rubber are mixed in a mass ratio of 90:10, and deionized water is added to disperse them uniformly to obtain a coating composition slurry. The remaining steps are the same as Example 1-1.

[0095] Comparative Example 3 The difference between Comparative Example 3 and Example 1-1 is that melamine cyanurate fiber and adhesive styrene butadiene rubber are mixed in a mass ratio of 90:10, and deionized water is added to disperse them uniformly to obtain a coating composition slurry. The remaining steps are the same as Example 1-1.

[0096] Comparative Example 4 The difference between Comparative Example 4 and Example 1-1 is that the boehmite filler, alumina fiber and adhesive styrene-butadiene rubber are mixed in a mass ratio of 60:30:10, and deionized water is added to disperse them uniformly to obtain a coating composition slurry. The remaining steps are the same as Example 1-1.

[0097] Relevant tests for coating compositions: (1) Content of miscellaneous elements Remove the diaphragm from the lithium-ion battery and select the diaphragm in the head, tail or super anode area of ​​the lithium-ion battery, where the diaphragm is not bonded to the pole piece and the coating is not transferred to the pole piece surface. Wash the diaphragm with NMP to remove the electrolyte and residual lithium salt, remove the coating from the surface of the base film, and dry it. Use an elemental analyzer to obtain the quantitative carbon and nitrogen element ratio in the coating.

[0098] (2) Length and width of fiber material Remove the diaphragm from the lithium-ion battery and select the diaphragm in the head, tail or super anode area of ​​the lithium-ion battery, where the diaphragm is not bonded to the pole piece and the coating is not transferred to the pole piece surface. Wash the diaphragm with NMP to remove the electrolyte and residual lithium salt. Use a scanning electron microscope to obtain the morphology of the diaphragm coating, and use a rectangular frame to take the length and width of 30 fiber materials, and calculate the average value of their length and width respectively, so as to obtain the length and width of the fiber material.

[0099] (3) Filler particle size Dv50 The coating was removed from the lithium-ion battery, cleaned with NMP to remove the electrolyte and residual lithium salt, dried, and then dispersed in deionized water to obtain a suspension of particles. The filler Dv50 was measured using a laser particle size tester.

[0100] Related performance tests of diaphragms (1) Heat retention rate test method: At a rated temperature and time, the dimensional change of the membrane coated with the coating composition is detected.

[0101] The diaphragm was cut into the rated size, with a length of A0 and a width of B0. The diaphragm was then placed in a forced air drying oven at 130°C for 1 hour, and the length A1 and width B1 of the diaphragm were measured under a microscope. The length and width retention rates of the diaphragm were obtained according to the following formulas.

[0102] Length thermal retention rate = A1 / A0*100% Width heat retention rate = B1 / B0*100% (2) Diaphragm porosity test method: The gas displacement method is used, and the test instrument is a true density tester (AccuPyc II1340). The diaphragm is cut into the rated size, with length A0, width B0, and thickness C0. The diaphragm's V0 space volume = A0*B0*C0 is calculated. The diaphragm is placed in the true density tester, and the true volume is measured as V1.

[0103] Porosity of diaphragm = (V0-V1) / V1*100% (3) Diaphragm impedance test method: EIS impedance test (a) Before measuring EIS, symmetrical batteries with different numbers of separator layers were placed in a high and low temperature box at 0°C for half an hour, and the EIS impedance spectrum was measured at the set temperature of 0°C; (b) The EIS conditions were set to 1 MHz-1 kHz, and the perturbation voltage was set to 5 mV. After the test, the data were linearly fitted to obtain the ionic impedance of the membrane.

[0104] (4) Testing method for coating thickness and diaphragm thickness: The diaphragm was disassembled from the lithium-ion battery, rinsed with NMP to remove the electrolyte and lithium salt of the diaphragm, dried at 60°C, and the diaphragm cross section was plasma cut. The cross-sectional morphology of the diaphragm was obtained by scanning electron microscopy (SEM), and the thickness of the coating and base film layers were measured.

[0105] Performance testing of lithium-ion batteries (1) Thermal safety performance test: At room temperature, charge the lithium-ion battery at a constant current of 0.5C until the voltage is higher than 4.45V, and further charge at a constant voltage of 4.45V until the current is lower than 0.05C. At this time, the lithium-ion battery is in a fully charged state. Place the lithium-ion battery in an oven and heat it at a rate of 10℃ / min until it reaches a specific temperature, such as 130℃, and keep it for one hour. If the lithium-ion battery does not catch fire or explode, it passes the temperature. Increase the specific test temperature by 2℃ step by step, and re-test the lithium-ion battery at this temperature to see if it passes, until the thermal runaway temperature of the lithium-ion battery is obtained.

[0106] (2) Low temperature impedance test: The lithium-ion battery was placed at 0°C for 30 minutes to allow the lithium-ion battery to reach a constant temperature state, and then charged at a constant current of 1C to a voltage of 4.45V, and then charged at a constant voltage to a current of 0.05C to allow the lithium-ion battery to reach a fully charged state, and the DC impedance of the lithium-ion battery was measured at this time.

[0107] (3) High temperature cycle test: The lithium-ion battery was placed at 45°C for 30 minutes to allow the lithium-ion battery to reach a constant temperature state, and then charged at a constant current of 1C to a voltage of 4.45V, and then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1C to a voltage of 3.0V, and the discharge capacity at this time was recorded as C0. The cycle test was performed for 100 cycles, and the discharge capacity at 100 cycles was recorded as C1.

[0108] Capacity retention rate = C1 / C0*100% (4) 2C discharge rate performance test: The lithium-ion battery was placed at 25°C for 30 minutes to reach a constant temperature state, and then charged at a constant current of 1C to a voltage of 4.45V, charged at a constant voltage to a current of 0.05C, and discharged at a constant current of 0.2C to a voltage of 3.0V. The discharge capacity at this time was recorded as C0. Then, the battery was charged at a constant current of 1C to a voltage of 4.45V, charged at a constant voltage to a current of 0.05C, and discharged at a constant current of 2C to a voltage of 3.0V. The discharge capacity at this time was recorded as C1. 2C discharge rate performance = C1 / C0*100%.

[0109] (5) Extrusion test: The lithium-ion battery was placed at 25°C for 30 minutes to allow the lithium-ion battery to reach a constant temperature state, and then charged at a constant current of 1C to a voltage of 4.45V and a constant voltage to a current of 0.05C.

[0110] In a 25°C test environment, place the lithium-ion battery on the test table, use a blunt nail with a diameter of 6mm, and a drop speed of 300N / Min. Test from the sample nickel Tab (starting from the head step, 10±1mm from the upper edge of the main body) until the lithium-ion battery explodes and catches fire, and record the extrusion force at this time.

[0111] See also Figure 2 and Figure 3 In the scanning electron microscope of the coating prepared in Example 1-1, in the above coating composition, the fiber material presents a rod-like structure, the fiber material and the filler particles are evenly distributed, and the filler particles are filled between the fiber materials.

[0112] See also Figure 4 In the scanning electron microscope of the coating prepared in Example 1-2, the fiber material presents a columnar structure, and the filler particles are filled between the fiber materials.

[0113] See also Figure 5 In the scanning electron microscope of the coating prepared in Comparative Example 2, the surface of the coating is dense and smooth, with fewer pores, and no fibrous material appears.

[0114] The above performance tests were performed on the lithium ion batteries prepared in the above examples and comparative examples, and the test data are recorded in the following table.

[0115] Table 1 Table 2 From Table 1 and Table 2, compared with Comparative Examples 1 to 3, the coating compositions in Examples 1-1 to 1-11 contain fiber materials and filler particles, which are applied to the diaphragm to improve the thermal safety performance of the diaphragm, and when the prepared diaphragm is applied to a lithium-ion battery, the lithium-ion battery has good rate performance, thermal safety performance, high-temperature cycle performance and extrusion resistance, and also reduces the low-temperature impedance of the lithium-ion battery. Compared with Comparative Example 4, when the coating compositions in Examples 1-1 to 1-11 contain miscellaneous elements, the rate performance, thermal safety performance and high-temperature cycle performance of the lithium-ion battery can be significantly improved.

[0116] Table 3 In Table 3, changing the ratio of the length to the width of the fiber material within the above-mentioned suitable range is beneficial to further improve the high temperature performance and thermal safety performance of the lithium ion battery, and is also beneficial to reduce the low temperature impedance of the lithium ion battery.

[0117] Table 4 Table 5 In Table 5, in Examples 1-16 to 1-23, the mass proportion of the impurity elements is changed, and the mass proportion of the impurity elements is within an appropriate range. The diaphragm has good high-temperature thermal retention rate, and the lithium-ion battery assembled therefrom has good rate performance, thermal safety performance, and mechanical extrusion resistance.

[0118] Table 6 Table 7 It can be seen from Tables 6 and 7 that when the length of the fiber material is adjusted and the length of the fiber material is within an appropriate range, the separator also has a good high-temperature heat retention rate. When applied to lithium-ion batteries, the lithium-ion batteries also have good rate performance, thermal safety performance and mechanical extrusion resistance. When the length of the fiber material is between 2 μm and 50 μm, its lithium-ion battery can also be compatible with excellent rate performance, thermal safety performance and mechanical extrusion resistance.

[0119] Table 8 Table 9 It can be seen from Tables 8 and 9 above that when the particle size Dv50 of the filler particles is within an appropriate range, the diaphragm also has a good thermal retention rate. When applied to lithium-ion batteries, the lithium-ion batteries also have good rate performance, thermal safety performance and mechanical extrusion resistance.

[0120] When the type of binder in the coating composition is changed, the separator also has a good heat retention rate. When it is applied to a lithium-ion battery, the lithium-ion battery also has excellent rate performance, thermal safety performance and mechanical extrusion resistance.

[0121] Table 10 In Table 10, by changing the thickness of the coating, the separator also has good high-temperature thermal retention and low impedance. When applied to lithium-ion batteries, the lithium-ion batteries also have good rate performance, thermal safety performance, mechanical extrusion resistance and low impedance performance.

[0122] By adjusting the mass ratio of the sum of the mass of the fiber material and the filler particles to the mass ratio of the binder and adjusting the porosity of the diaphragm, when applied to lithium-ion batteries, the lithium-ion batteries also have good rate performance, thermal safety performance, mechanical extrusion resistance and low impedance performance.

[0123] The above disclosure is only a preferred implementation mode of the present application, and certainly cannot be used to limit the present application. Therefore, equivalent changes made according to the present application are still within the scope covered by the present application.

Claims

1. A coating composition, characterized in that The coating composition comprises a fiber material, filler particles and a binder, wherein the fiber material comprises at least one of a first inorganic ceramic or a first organic matter containing a heteroelement, the filler particles comprise at least one of a second inorganic ceramic or a second organic matter containing a heteroelement, at least one of the fiber material and the filler particles is an organic matter containing the heteroelement, the heteroelement comprises nitrogen and / or phosphorus, and the mass percentage of the heteroelement is 10% to 60% based on the mass of the coating composition.

2. The coating composition according to claim 1, characterized in that The coating composition satisfies at least one of the following conditions: (1) The ratio of the length to the width of the fiber material is (3-50):1; (2) The length of the fiber material is 2 μm to 50 μm; (3) The particle size Dv50 of the filler particles is 0.1 μm to 3 μm; (4) The mass ratio of the fiber material to the filler particles is 1:(1-10); (5) Based on the mass of the coating composition, the mass percentage of the impurity element is 15% to 45%; (6) In the coating composition, the mass ratio of the sum of the mass of the fiber material and the filler particles to the mass ratio of the binder is 99:1 to 85:

15.

3. The coating composition according to claim 1 or 2, characterized in that The first organic matter includes at least one of ammonium polyphosphate, dicyandiamide, piperazine pyrophosphate, melamine polyphosphate, polyacrylonitrile, melamine, melamine thiocyanate or melamine cyanurate.

4. The coating composition according to claim 1 or 2, characterized in that The first inorganic ceramic includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, aluminum oxide, boehmite, titanium dioxide, aluminum silicate, silicon carbide, and silicon nitride.

5. The coating composition according to claim 1 or 2, characterized in that The second organic matter includes at least one of polyacrylonitrile, ammonium polyphosphate, melamine, dicyandiamide, melamine cyanurate, melamine thiocyanate or melamine polyphosphate.

6. The coating composition according to claim 1 or 2, characterized in that The second inorganic ceramic includes at least one of lithium aluminum titanium phosphate, lithium lanthanum titanate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium niobium oxide, aluminum oxide, boehmite or magnesium hydroxide.

7. The coating composition according to claim 1 or 2, characterized in that The binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber, isocyanate, polyvinyl alcohol or sodium carboxymethyl cellulose.

8. A diaphragm, characterized in that: The separator includes a base film and a coating layer located on at least one surface of the base film, wherein the coating layer includes the coating composition according to any one of claims 1 to 7.

9. The diaphragm according to claim 8, characterized in that The diaphragm satisfies at least one of the following conditions: (1) The porosity of the diaphragm is 35% to 50%; (2) The thickness of the coating is 0.3 μm to 5 μm.

10. An electrochemical device, comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The electrochemical device further comprises the separator as claimed in claim 8 or 9, wherein the separator is located between the positive electrode sheet and the negative electrode sheet.

11. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 10.

Citation Information

Patent Citations

  • Composite diaphragm material and preparation method and application thereof

    CN104409674A

  • Ceramic slurry, ceramic diaphragm and lithium ion battery

    CN109411683A

  • Modified diaphragm of metal negative electrode battery, preparation method and application

    CN110828749A

  • Diaphragm for lithium ion battery, preparation method of diaphragm and lithium ion battery

    CN111446404A

  • High-temperature-resistant integrated lithium battery diaphragm and preparation method thereof, and mixed coating

    CN111509171A

Cited By

  • Composite diaphragm, preparation method thereof and secondary battery

    CN121939095A

  • Composite separator and method for manufacturing the same, secondary battery

    CN121939095B

  • Coating composition, separator, electrochemical device, and electronic device

    WO2026103895A1